Uptake of funded influenza vaccines in young Australian children in 2018; parental characteristics, information seeking and attitudes. Issue 2 (10th January 2020) - Frawley, Jane E.; McManus, Korie; McIntyre, Erica; Seale, Holly; Sullivan, Elizabeth
Abstract: Objective: Infants and children under 5-years are at an increased risk of complications from influenza. We aimed to evaluate characteristics associated with uptake of Australian state and territory funded influenza vaccine programs in 2018 for children aged 6-months to 5-years. Materials and methods: A national online survey of 1002 Australian parents with at least one child aged between 6-months and 5-years (response rate 29.9%). A 23-item online questionnaire asked parents about health service use, 2017 and 2018 influenza vaccine uptake, and routine childhood vaccine status for their youngest child. Parents were also asked a range of questions about their demographics, sources of vaccine information, and beliefs and attitudes towards immunisation. Results: A total of 1002 parents completed the questionnaire and 52.9% of children aged 6-months to 5-years in our sample were immunised against influenza in 2018; representing a significant increase from 2017. Knowing the vaccine was free for their child, and being influenced by a pharmacist increased the likelihood that their child received the influenza vaccine. Not receiving an influenza vaccine recommendation from a health care provider significantly reduced the likelihood of immunisation. Some parents were worried about the safety of the influenza vaccine for their child (36.4%), while 26.5% of parents agreed that you can catch influenza from the vaccine. Conclusions: Uptake of influenza vaccine for Australian children aged 6-months to 5-years increased significantly in 2018. Continuing efforts to build parents' trust in childhood influenza vaccination are still required. Increasing opportunities for health care providers to recommend vaccination will lead to further improvements in uptake for young children.